Peer Support in Coordination of Physical Health and Mental Health Services for People With Lived Experience of a Serious Mental Illness - Storm, Marianne; Fortuna, Karen L.; Brooks, Jessica M.; Bartels, Stephen J. (Frontiers in Psychiatry, 2020)
Background: Engaging peer support to augment and enhance traditional mental health services presents novel opportunities to improve service engagement and delivery. However, there has not been an in-depth analysis of the processes and methods behind the coordination of medical and mental health care by peer support specialists. Study aim: To explore the potential of peer support specialists in community mental health centers and as a means to improve coordination of medical and mental health services for people with a serious mental illness. Methods: We conducted 28 semi-structured qualitative interviews with peer support specialists and mental healthcare professionals in community mental health centers in two states [blinded for review] in the United States. Data were triangulated to explore peer support specialists and mental health professionals’ perspectives. Results: We found five themes characterizing the role of peer support services in the coordination of medical and mental health services for individuals with serious mental illness: (1) Advocacy in interprofessional meetings; clinical teams, and advisory councils; (2) Sharing lived experiences and connecting with available resources and services; (3) Preparing for mental health and medical care visits; (4) Mutuality; (5) Affiliations, funding, and sustainability of peer support services. Conclusion: This study suggests that peer support specialists can uniquely contribute to the coordination of medical and mental health services for individuals with serious mental illness.